2007
DOI: 10.1021/tx7002195
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Metabolism of Combretastatin A-1 Produces Quinone Intermediates with the Potential To Bind to Nucleophiles and To Enhance Oxidative Stress via Free Radicals

Abstract: Combretastatins are stilbene-based, tubulin depolymerization agents with selective activity against the tumor vasculature; two variants (A-1 and A-4) are currently undergoing clinical trials. Combretastatin A-1 (CA1) has a greater antitumor effect than combretastatin A-4 (CA4). We hypothesized that this reflects the enhanced reactivity conferred by the second (ortho) phenolic moiety in CA1. Oxidation of CA1 by peroxidase, tyrosinase, or Fe(III) generates a species with mass characteristics of the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 54 publications
1
54
0
Order By: Relevance
“…High vascular permeability is considered a predisposing factor for response to CA-4-P (36), and chronic NOS inhibition may impact on vascular permeability by encouraging leukocyteendothelial interactions (37). Induction of reactive oxygen species by CA-4-P is likely to constitute at least part of the mechanism of action of the drug (38,39), and leukocyte-endothelial interactions and reduced levels of NO may direct reactive oxygen species induction along a more damaging pathway under chronic NOS inhibition. NOS inhibition has also been shown to increase RhoA activity (40), a pathway activated by CA-4-P, at least in vitro (41).…”
Section: Discussionmentioning
confidence: 99%
“…High vascular permeability is considered a predisposing factor for response to CA-4-P (36), and chronic NOS inhibition may impact on vascular permeability by encouraging leukocyteendothelial interactions (37). Induction of reactive oxygen species by CA-4-P is likely to constitute at least part of the mechanism of action of the drug (38,39), and leukocyte-endothelial interactions and reduced levels of NO may direct reactive oxygen species induction along a more damaging pathway under chronic NOS inhibition. NOS inhibition has also been shown to increase RhoA activity (40), a pathway activated by CA-4-P, at least in vitro (41).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unexplained why the trans-isomer of compound 6 affects tubulin polymerization in the same way as methoxystilbenes in the cis configuration, which share high structural similarity with CA-4. The tubulininterfering activity of trans-isomers that leads to cell cycle arrest [56,99] still needs to be elucidated. Cai et al [62] synthesized six new stilbene derivatives and screened for cytotoxicity in different human tumor cell lines.…”
Section: Tubulin-binding Stilbenes As Vdasmentioning
confidence: 99%
“…Most recently, it was shown that the cis isomer of CA-1P significantly impaired tumor blood flow leading to secondary tumor cell death and more than 95% tumor necrosis 24 h post drug exposure. It was suggested that CA-1P may be metabolized to orthoquinone intermediates leading to the formation of cytotoxic free radicals [99]. Treatment with the trans-isomer had no effect on the blood flow parameters.…”
Section: Tubulin-binding Stilbenes As Vdasmentioning
confidence: 99%
“…It is a synthetic, phosphorylated prodrug of combretastatin A1 (OXi4500), a naturally occurring derivative from the bark of the South African bush willow tree, Combretum caffrum, that reversibly binds to the b-subunit at the colchicine-binding site of tubulin to inhibit microtubule assembly (3,4). It is metabolized to a reactive orthoquinone species that is also assumed to be directly cytotoxic in tumor cells (5,6) because of the production of a quinone metabolite that could bind to nucleic acids and also produces free radicals leading to the enhancement of oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%